Injuries Resulted From Breastfeeding: A New Approach To A Known Problem - Marina Possato Cervellini; Mônica Antar Gamba; Kelly Pereira Coca; Ana Cristina Freitas de Vilhena Abrão (SciELO, 2014)
This study aimed at analyzing nipple trauma resulted from breastfeeding based on dermatological approach. Two integrative reviews of literature were conducted, the first related to definitions, classification and evaluation methods of nipple trauma and another about validation studies related to this theme. In the first part were included 20 studies and only one third defined nipple trauma, more than half did not defined the nipple's injuries reported, and each author showed a particular way to assess the injuries, without consensus. In the second integrative review, no validation study or algorithm related to nipple trauma resulted from breastfeeding was found. This fact demonstrated that the nipple's injuries mentioned in the first review did not go through validation studies, justifying the lack of consensus identified as far as definition, classification and assessment methods of nipple trauma.